1979
DOI: 10.1007/bf01876114
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by HCO 3 − of Na+ transport in rabbit gallbladder

Abstract: Bicarbonate presence in the bathing media doubles Na+ and fluid transepithelial transport and in parallel significantly increases Na+ and Cl- intracellular concentrations and contents, decreases K+ cell concentration without changing its amount, and causes a large cell swelling. Na+ and Cl- lumen-to-cell influxes are significantly enhanced, Na+ more so than Cl-. The stimulation does not raise any immediate change in luminal membrane potential and cannot be due to a HCO3(-)-ATPase in the brush border. The stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
2

Year Published

1982
1982
1997
1997

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 43 publications
(56 reference statements)
6
36
2
Order By: Relevance
“…Experiments were designed based on the knowledge that no C1-conductance exists at the apical membrane of rabbit gallbladder Cremaschi & Meyer, 1982). Moreover, total cellular C1-influx is Na+-dependent (Cremaschi & Hrnin, 1975;Cremaschi, H6nin & Meyer, 1979;Cremaschi et al, 1983) and inhibited by SCN- (Cremaschi et al, 1979(Cremaschi et al, , 1983.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were designed based on the knowledge that no C1-conductance exists at the apical membrane of rabbit gallbladder Cremaschi & Meyer, 1982). Moreover, total cellular C1-influx is Na+-dependent (Cremaschi & Hrnin, 1975;Cremaschi, H6nin & Meyer, 1979;Cremaschi et al, 1983) and inhibited by SCN- (Cremaschi et al, 1979(Cremaschi et al, , 1983.…”
Section: Introductionmentioning
confidence: 99%
“…All this indicates, for both species, an increased dissociation of polyelectrolytes from protons, which is mainly compensated with free K+ concentration in the guinea-pig and with bound Na+ in the rabbit. Previous results obtained in the rabbit (Cremaschi & Henin, 1975a;Cremaschi et al 1979) also indicated that only a fraction of cellular Na+ was rapidly exchangeable with 22Na.…”
Section: Discussionmentioning
confidence: 80%
“…It is noteworthy that, in spite of the fact that HCO3-does not affect the apical conductive Na+ pathways, it significantly diminishes the apical electromotive force because of the decrease in the cell K+ activity it elicits and because of the dominant conductance of this cation at both cell aspects (Henin & Cremaschi, 1975;Cremaschi & Henin, 1975a). Thus, in the rabbit the apical electromotive force (Em), calculated (Cremaschi & Henin 1975a, b;Cremaschi et al 1979). More precisely K+ concentration is 184-1 ±4-5 mm (5) and 117-2 + 5-4 mm (13); Na+ concentration is 6-6 + 2-1 mm (5) and 58-7 + 4.9 mm (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 42 + 05 nequiv cm-2 h-1 (13 exp.) were SCN--and Na+-insensitive (junctional component; Cremaschi & Henin, 1975;Cremaschi, Henin & Meyer, 1979;Cremaschi et al 1983). At maximal effects 10-3 M-amiloride, 10-4 M-SITS and 5-5 x 10-5 M furosemide only about halved the cellular component of Cl-influx (SCN--and Na+-sensitive).…”
Section: By M Chowdhury and Marianne Fillenz University Laboratory mentioning
confidence: 99%